Strengthening Islamic Character Education in the Perspective of the Merdeka Curriculum - Darmanto, Darmanto; Asroriah, Fatimatul; Istiqomah, Istiqomah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2025)
The character crisis among today’s young generation has become a serious concern in the field of education, particularly within Islamic education. The Merdeka Curriculum, as the latest educational policy in Indonesia, offers flexibility and a value-based approach that is considered promising for strengthening Islamic character education in schools. This study aims to explore and analyze the relationship between the Merdeka Curriculum and the reinforcement of Islamic character education, both conceptually and in practical implementation. This research employs a qualitative approach using the library research method. Data were collected through literature reviews of books, scientific journals, policy documents, and educational practice reports relevant to the topic. The analysis was conducted descriptively and analytically by linking Islamic educational theory with national curriculum policies. The findings indicate that the Merdeka Curriculum contains characteristics that support the internalization of Islamic values, such as differentiated learning, character-strengthening projects through the Pancasila Student Profile, and contextual space for religious values in the learning process. Best practices observed in Islamic-based schools show that teacher role modeling, religious routines, and parental collaboration play essential roles in shaping students' Islamic character. This study concludes that the Merdeka Curriculum provides a strategic opportunity to revitalize Islamic educational values holistically and in line with contemporary educational challenges.